Identifying barriers and potential solutions to improve equitable access to community eye services: an exploratory sequential mixed methods study protocol - Min Kim; David Macleod; Michael Gichangi; Andrew Bastawrous; Matthew J Burton; Jacqueline Ramke; Oathokwa Nkomazana; Sailesh Mishra; Shalinder Sabherwal; Luke Nelson Allen; Abhishek Roshan; Sarah Karanja; et al. (BMJ Open)
Introduction Access to care varies by sociodemographic group, with some groups facing higher barriers to care than others. This study will use novel methods to explore barriers and potential solutions as perceived by members of the population groups who are least able to access care. We aim to use rapid yet robust mixed methods that allow us to identify generalisable findings within each programme and testable service modifications to improve equitable access to care; delivering non-tokenistic findings within a matter of weeks.Methods and analysis This is a multiphased exploratory sequential mixed methods study. We will use the same approach in four different screening programmes, in Botswana, India, Kenya and Nepal. First, we will conduct interviews with people purposively selected from the sociodemographic subgroups with the lowest odds of accessing care within each programme. We will explore their perceptions of barriers and potential service modifications that could boost attendance at eye clinics among people from these ‘left-behind’ groups. We will use a deductive analytic matrix to facilitate the rapid analysis of qualitative data. Space will be made for the inductive identification of themes that are not necessarily captured in the framework. Sample size will be determined by thematic saturation. Next, we will conduct a survey with a representative sample of non-attenders from the same left-behind groups, asking them to rank each suggested service modification by likely impact. Finally, we will convene a multistakeholder workshop to assess each service modification based on ranking, likely impact, feasibility, cost and potential risks. The most promising service modifications will be implemented and evaluated in a follow-on randomised controlled trial, the methods for which will be reported elsewhere.Ethics and dissemination This project has been approved by independent research ethics committees in Botswana, Kenya, India, Nepal and the UK. We will disseminate our findings through local community advisory boards, national eye screening meetings, in peer-reviewed journals and at conferences.